An Innovative Approach for Extraction of Energy from Waste Heat Dissipation from Vehicle Engine Heat-up - More, Ashlesha (Journal of Advanced Research in Signal Processing and Applications, 2021)
Nowadays the need of energy increases day by day but only few sources of energy are available to produce or generate energy as our fuel resources are nearly coming to end. There are needs to be ways to use waste heat energy. There are some technologies which implement the recycling of waste heat by which waste heat can be trapped and recycle and reutilized. Most of the techniques currently available recover waste heat in the form of thermal energy which is then converted into electricity in a conventional thermal power plant. This production of energy efficiently from waste heat, thermoelectric generator module is used which works on See back Effect. Here, the power generation is simple, as there is need of only temperature difference to produce power but our method of conversion is something innovative by using the TEC (thermo electric cooler), we are converting the heat energy to low voltages with the help of temperature differences that was created. Hence the voltages are very low so we are using the DC-DC boosters and buck converters, so that high amount of voltages is generated and stored in the battery and can use it for long time. Presently 65% of production of energy in automobiles is wasted in form of heat by exhaust gases. This paper tries to prove the feasibility of conversion of heat energy radiated from vehicle engine to produce electricity. As our system can work in any conditions and so it is very useful for daily life. Also it is capable of changing the whole automotive industry which is totally related to our system. By using this, energy is used to charge the mobile electronics, run home appliances, dc lighting. How to cite this article: More A, Patil D, Warungse M et al. An Innovative Approach for Extraction of Energy from Waste Heat Dissipation from Vehicle Engine Heat-up. J Adv Res Sig Proc Appl 2019; 1(2): 1-13